RANCANG BANGUN MESIN SORTIR BUAH TOMAT BERDASARKAN TINGKAT KEMATANGAN DENGAN SENSOR TCS3200 - Puspita, Desi; Gusmaliza, Debi; Aminah, Siti (LPPM UNIVERSITAS BINA INSAN, 2025)
The tomato sorting process is currently still done manually by farmers where the results are less accurate and effective. Currently, many still use the manual tomato separation process, so it takes a long time and is not accurate in the process of separating tomatoes. The ripeness of tomatoes can be determined during the harvest process. The level of ripeness of tomatoes is seen from their color, ripe fruit is marked with red. The purpose of the study was to create a prototype for automatic tomato sorting based on the level of ripeness with the TCS3200 sensor. The TCS3200 sensor plays a role in detecting the level of ripeness of tomatoes based on the color of the tomato skin. The system development method used is the Rapid Application Development (RAD) system such as Requirements Planning, RAD Workshop Design, and Implementation. This prototype will work by selecting the color of red, greenish, and yellow tomatoes. This tool is equipped with a motor to separate tomatoes according to the level of ripeness, a TCS3200 color sensor that produces three identification outputs, namely 100% ripe tomatoes, 80% unripe, and 100% half-ripe with an overall identification level of 93.3%.